Carlo Tognato (ed.), Cultural agents reloaded: the legacy of Antanas Mockus - Santiago Silva Jaramillo (Eunomia, 2021)
Este artículo reseña: Carlo Tognato (ed.), Cultural agents reloaded: the legacy of Antanas Mockus, (2017) Harvard University Press Cambridge, 646 pp.